(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Vascular encephalopathy (VE) is a critical cause of cognitive impairment but the correlation between neuroimaging abnormalities and clinical severity is unknown. A retrospective study was conducted on 81 patients with MRI-proved VE to investigate correlations of imaging measures with clinical rating scales. These individuals underwent standard 3T MRI with quantitation of atrophy patterns on the Global Cortical Atrophy scale and white matter lesions on the Fazekas scale. Clinical severity was quantified with the Stephen-Porges autonomic dysfunction scale and PSM25 neurologic deficit scale. The study revealed correlation of severity of atrophy in the frontal lobe with respect to PSM25 scores (β=0.76, p<0.001), accounting for 58% variance in scores. The burden of white matter lesions was strongly correlated with autonomic dysfunction (r=0.65, p<0.001). Male individuals had greater ischemic changes than female individuals (mean Fazekas grade 2.4 vs 1.8, p=0.02). The study confirms the clinical use of visual rating scales in the diagnosis of VE and sets the stage for the primary role of the integrity of the frontal lobe in the concomitant neurologic deficits.